Pattern of nodal metastasis of cutaneous squamous cell carcinoma involving the temporal bone. Issue 1 (16th December 2022) - Hintze, Justin M.; O'Riordan, Isobel; Jones, Holly; McHugh, Alison; Gendre, Adrien; Timon, Conrad; Kinsella, John; Lennon, Paul; Walsh, Rory McConn; Shine, Neville; O'Neill, James P.
Abstract: Objective: The objective of this study was to explore the pattern of lymph‐node spread of SCCs involving the temporal bone. Methods: We retrospectively reviewed all cutaneous SCCs involving the temporal bone over a 20‐year time‐period. Forty‐one patients were eligible. Results: Mean age was 72.8 years. The diagnosis was cutaneous SCC in all cases. All patients underwent a temporal bone resection, 70.7% had a neck‐dissection and 78.0% a parotidectomy. Level 2 was the most common area of neck metastasis, and occurred in 12.2%. The parotid had disease in 34.1%. 51.2% of patients underwent free‐flap reconstruction. Mean overall survival of the cohort was 4.2 years. Conclusions: Overall, the rate of cervical nodal metastasis was 22.0% and 13.5% in the occult setting. The parotid was involved in 34.1% and 10.0% in the occult setting. Results from the present study support consideration for performing a parotidectomy at the time of temporal bone resection, while a neck dissection can be performed for adequate staging of the nodal basin. Level of Evidence: 3 Abstract : The objective of the present study was to evaluate the pattern of spread of SCCs involving the temporal bone. The risk of cervical and parotid metastasis was 22.0% and 34.1%, respectively, while the risk of occult disease was 13.5% and 10.0%, respectively.